Advances in Solid Oxide Fuel Cells: Review of Progress through Three Decades of the International Symposia on Solid Oxide Fuel Cells. (30th May 2017) - Minh, Nguyen; Mizusaki, Junichiro; Singhal, Subhash C.
Abstract : Solid oxide fuel cell (SOFC) technology has made significant progress in the past 30 years and is currently in the early commercialization stage. The progress of the technology can be seen clearly through review of the papers and presentations at the biennial series of International Symposium on Solid Oxide Fuel Cells initiated in 1989. This paper details the growth and evolution of the Symposium series as the technology progressed and highlights key advances in materials development, understanding of electrode reactions and chemical interactions, and design, performance, durability and operation of SOFC single cells, multi-cell stacks and power systems as documented in the Symposium publications.